2009
DOI: 10.1111/j.1460-9568.2009.06924.x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral habenula projections to dopamine and GABA neurons in the rat ventral tegmental area

Abstract: Ventral tegmental area (VTA) dopamine (DA) neurons and their forebrain projections are critically involved in reward processing and cognitive functions. Descending projections from the lateral habenula (LHb) play a central role in inhibiting DA cell activity in response to the absence of expected rewards. As LHb efferents are reportedly glutamatergic, their ability to inhibit DA cells would theoretically require a disynaptic connection involving VTA GABA neurons and their local collateral inputs to DA cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
175
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(200 citation statements)
references
References 77 publications
(152 reference statements)
18
175
1
1
Order By: Relevance
“…This is supported by anatomical data indicating that the LHb receives input from forebrain nuclei, whereas its efferents terminate in midbrain dopamine (DA) areas, such as the ventral tegmental area (VTA) and substantia nigra, as well as serotonergic brain regions (Herkenham and Nauta, 1979;Araki et al, 1984;Behzadi et al, 1990;Omelchenko et al, 2009). Many studies implicate these monoamine neurons in motivation, reward, and psychiatric illness, suggesting that the LHb may be involved in these behavioral phenomena .…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…This is supported by anatomical data indicating that the LHb receives input from forebrain nuclei, whereas its efferents terminate in midbrain dopamine (DA) areas, such as the ventral tegmental area (VTA) and substantia nigra, as well as serotonergic brain regions (Herkenham and Nauta, 1979;Araki et al, 1984;Behzadi et al, 1990;Omelchenko et al, 2009). Many studies implicate these monoamine neurons in motivation, reward, and psychiatric illness, suggesting that the LHb may be involved in these behavioral phenomena .…”
Section: Introductionmentioning
confidence: 66%
“…Physiological studies also support this role as there is an inverted relationship between LHb and DA neuron activity, and activation of the LHb strongly inhibits midbrain DA neuron firing (Ji and Shepard, 2007;Matsumoto and Hikosaka, 2007). There is evidence that the LHb, which is largely composed of glutamatergic neurons (Geisler and Trimble, 2008;Omelchenko et al, 2009), sends a direct projection to DA and non-DA neurons in the ventral midbrain Omelchenko et al, 2009). However, this is inconsistent with strong inhibition of DA neurons during LHb activation (Christoph et al, 1986;Ji and Shepard, 2007;.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Noteworthy, activity of DA and LHb neurons appears to be causally correlated, as electrical stimulation of the LHb inhibits DA neurons (Christoph et al, 1986;Ji and Shepard, 2007;Matsumoto and Hikosaka, 2007). However, the sparse innervation of DA neurons by excitatory LHb afferents (Brinschwitz et al, 2010;Omelchenko et al, 2009) unlikely explains this inhibition, and the presence of an area intermediate between the LHb and the VTA was originally postulated. Elegant studies by Jhou et al (2009a, b) revealed that g-aminobutyric acid (GABA) neurons in the rostromedial tegmental nucleus (RMTg), a region also denominated as 'tail' of the VTA (Perrotti et al, 2005), integrate input from the LHb and send output projection to midbrain DA neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Prema navedenim monoaminergičkim neuronima mezencefalona Å”alje glutamatergičke projekcije koje prave sinapse pretežno sa gaBaergičkim neuronima ventralnog tegmentalnog područja, substantiae nigrae i rostromedijalnog tegmentalnog jedra (6,22), koje inhibitorno deluju na dopaminergičke i serotonergičke neurone čiju aktivnost smanjuju. Međutim, opisan je i manji broj direktnih, ekscitatornih, glutamatergičkih projekcija lHb koje stižu do dopaminergičkih neurona mezencefalona (22)(23)(24).…”
Section: Funkcija Habenularnog Kompleksaunclassified